Petri nets methodology for the design and control of migration processes towards industry 4.0 - Cachada, Ana (2020)
The fourth industrial revolution, commonly known as Industry 4.0, germinated in Germany as an industrial program of the government to reinvigorate the manufacturing sector. Nowadays, this change in the industrial paradigm has reached a global scale and is proposing to transform the traditional factories into more competitive, efficient and productive industries. In order to accomplish this goal it is necessary to establish methodologies to migrate from the traditional systems to innovative systems, namely those applying the Cyber-Physical Production Systems (CPPS) concepts. This paper proposes a methodology based on the Petri nets formalism for the modelling, analysis, validation and simulation of the migration process during the design phase and the control and monitoring of such processes during the implementation phase.